KAJIAN PENGEMBANGAN DAN PENGELOLAAN EKOWISATA BAHARI DI PULAU PRAMUKA TAMAN NASIONAL KEPULAUAN SERIBU - Mariana, Siska; Nitibaskara, Tb. Unu; Susdiyanti, Tun (Jurnal Nusa Sylva, 2013)
The study was conducted at Scout Island Thousand Islands National Park (TNKpS). This study educational facilitiesas well asto know the management and development of marine aims to explore the potential of ecotourism in marine TNKpS Scout Island as a tourist attraction and ecotourism in TNKpS Scout Island. Research activities carried out at Scout Island Thousand Islands National Park (TNKpS). Research conducted from March to April 2013. Data processing wasperformed using Travel Attractions Assessment (2007) and subsequently analyzed using SWOT. SWOT analysisis used to determine the priority of alternative strategies most appropriate development carried out with consideration of internal and external factors. Internal factors are the strengths and weaknesses while the external factors are opportunities and threats.